The Effectiveness of Football Learning in Improving Basic Technical Skills of Physical Education Students at Dahasen University, Bengkulu - Apriansyah, Dolly (Universitas Majalengka, 2025)
This study aims to analyse the effectiveness of soccer learning in improving the basic technical skills of Physical Education students at Dahasen University, Bengkulu. The research method used was quasi-experimental with a one-group pretest-posttest design. The study subjects were 30 students who participated in soccer learning for eight meetings. The data collection instrument was a basic technical skills test, including passing, dribbling, shooting, and ball control. Data was analysed using a paired sample t-test and effect size calculation (Cohen’s d). After learning, the results showed a significant increase in all aspects of basic techniques (p <0.05). The effect size values ​​for all basic methods were included in the vast category (Cohen’s d> 2.00), indicating that learning strongly impacted improving skills. These findings confirm that soccer learning based on drills and small-sided games effectively develops students’ basic technical skills. This study recommends the application of a varied, practical, and applicable learning approach in teaching soccer in a physical education environment to produce technically and pedagogically competent graduates.